Decode Startup Business Entrepreneurial Management in Thailand 4.0 - Phungphol, Wilai; Sungrugsa, Narin (Dusit Thani College Journal, 2020)
The objectives of this research were 1) to study business management ideologies of entrepreneurs to be the leader of innovative startup business for sustaining in Thailand 4.0 2) to study the practices on discourse from startup entrepreneurs and the authority knowledge of discourse on startup business in contemporary Thailand 4.0 and 3) to study the way to create more entrepreneurs to have better consciousness to do the business in sustainable thai society. The research was the postmodernism and qualitative methodology with deciphering as the guideline for most descriptive and analytical purposes by using 11 key informants from purposive selection. The study tools would be in-depth interview and participatory observation by using phenomenological approach and decode of discourse on startup management informants by using narrative approach. Based on the findings found the ideologies that adhered the managing startup business issues to be the leader of the outstanding business performance, learn new technology, do business for success quickly by not too much relying on financial support sources that compared a new discourse says Jack who made a giant capitalist with high power fall down proudly. For the power support,there were deep experts, using world wide social media and after sales service concept for customer trust that made a new experience and compared the discourse says Miniature Business, Excellent idea, wizard management. Approach the globalization from the findings came from core new experiences by doing difficult counterfeit products, make alliances with major capitalists/multinationals to be a new experience that compared a new discourse says Fast fish eat big fish startup entrepreneurs become Small fish, nimble, courageous, aggressive, grazing fish eat big fish. The last findings focused on supporting from government in accelerative force continuously as follows 1) “Stability, Prosperity, Sustainability from government’s policy. 2) Government subsidization. 3) Speed up knowledge and skills on implementation. 4) Sending a team of consultants who give advice to follow the strict ideological that compared the discourse says “In term of Talent entrepreneur must be a good man and knowledge of moral merit” to make sustainable startup business. Based on the findings found the practices on power of knowledge, decode the discourse of startup business entrepreneurial management in Thailand 4.0: 1) Monopolized production by patents. 2) Produce products to meet customer satisfaction continuously. 3) Create a customer experience to buy quality products to fulfill the missing of the pain point. Based on the findings found theways to create new entrepreneurs becoming experts require the government side cope with: 1)1 year and 5 years training and developmentplan. 2) Provide consultant to advice startup entrepreneurs to create a successor continuously to work and businessand concrete action that we mention in Smart Thai Entrepreneur in Thailand 4.0 or In English version cited for Being a Talented Man (BATMAN).